(untitled) (Nóema, 2013)
The first issue (2010) of Noema had asked about the public space of philosophy, how and where its practice of work and thought express itself in an effective way, and which was its relationship with everybody’s living experience, in particular with their political life. In the second issue (“Objectivity and Realism: the Last Enterprise of Truth”), whose development is still in progress, the question concerned that working space which is connected with the sense of truth of the philosophical practice, for instance its claim to be objective in speaking and writing, which articulates it as an extreme inquiry of what would be the “reality” in which we find ourselves to live. The third issue asks a complementary and correlative question: provided that we can come to an agreement about what would be, in philosophy, the sense of truth of its “objects”, the objective reality of its operations and expressions, the common and universal value of its practices of inquiry, what then would be the “places and figures of the subject”, both the philosophical and generally human subject? We do not need to remind ourselves that the question of the subject has dominated the twentieth century in very suggestive and often dramatic ways: we come from the “philosophy of suspect” (Marx, Nietzsche and Freud), which considered the subject, the self-conscious I, as an illusory and extreme manifestation of underground forces that kept him or her under their power, as a product of material and economic practices that escaped his or her control and immediate comprehension: the subject is a “battlefield”, a “dividual” even before being an individual, a relative figure in time, history and the play of cultures. In another sense the subject, toward which the desperate and self-knowingly problematic effort of Husserl was directed, seems to be an existential “I”, always “threw” in a destiny of alienation, a destiny which philosophy would perhaps not be able to redeem; the subject is nothing more than a “grammatical” figure, the punctual expression of the mechanisms of power; or, finally, it is the result of a story which only biology would be able to tell: a neuronal “precipitated”, at most accompanied by superstructurally transient social imaginations and moral needs. We have these and other questions behind us, but they are still the living objects of many our discussions. To re-propose the question of the subject – the question about its philosophical places and effective figures – seems useful, if not indispensable, in order to deepen and clarify that which is an essential aspect of the practice of philosophy: what subject does speak in it? Which figure of truth, if any? Or maybe there are more than one? Or none? We would like this question to be explored in the broadest and freest way. As they say, at 360 degrees.